Mr volumetry study of hippocampus and temporal lobe in malay adults with normal mri brain in HUSM - Dali, Roziah (2011)
Introduction: Volumetry of hippocampus and temporal lobe has been paid attention more and more along with advanced in MRI. Magnetic resonance imaging (MRI) is a non-invasive and provides detailed, accurate morphology of hippocampus and also temporal lobe. MR volumetry of these two structures is important as they are affected by several disease processes. Establishing a normative data for a population is essential so as to refer and diagnose particular illness. There are computer aided automated and semi-automated method available for MR volumetry. This study used manual method for the normative data of hippocampus and temporal lobe. Volumetric MRI analysis is more sensitive than T2-weighted imaging to atrophy associated with hippocampal sclerosis. It also distinguish volume loss from space occupying lesion as well as may predict a good prognosis following surgery for epilepsy (Bronen, Cheung et al. 1991). The purpose of this study is to obtain hippocampal and temporal lobes volumes in normal Malay adults as a normative database. Hence, it can be a reference in diagnosing diseases related with these two structures. Objectives: The aims of this study is to determine the volume of hippocampus and temporal lobe in Malay adult with normal MRI brain. Methods and materials: This was a cross sectional observational study to determine volume of hippocampus and temporal lobe in Malay adult with normal MRI brain. The age of the patients was range from 21 to 49 years old. The study period was from February 2008 until June 2009 and 51 subjects were included. Majority of them were normal volunteers, and some were patients who had normal MRI brain. MRI of brain and temporal lobe series were performed using a Signa Horizon LX 1.0 Tesla from the Generic Electric Company. Oblique coronal sections perpendicular to the axis of hippocampus were done with 4mm slice thickness and 1mm gap. T1, T2, FLAIR and SPGR series were done. Hippocampal and temporal lobevolumetry were performed. The mean and standard deviation (SD) of hippocampus and temporal lobe volume were calculated using SPSS version 17. Results: Mean and standard deviation of the total hippocampus volume of normal adult was 6.43 cm3 (0.80) for all subjects. Mean total hippocampus volume was 6.62 cm3 (0.87) in male and 6.27 cm3 (0.71) for female. Mean and standard deviation of hippocampus were 3.35 cm3 (0.46) on the right and 3.01 cm3 (0.45) on the left side. Mean hippocampal volume for the right side for male subjects is ranging from 3.21 cm3 (0.44) to 3.54 cm3 (0.35) and for the left side is from 2.95 cm3 (0.30) to 3.32 cm3 (0.42). Mean hippocampal volume for the right side for female subjects is ranging from 3.07 cm3 (0.47) to 3.42 cm3 (0.30) and for the left side is from 2.80 cm3 (0.36) to 3.08 cm3 (0.25). Mean total temporal lobe volume for all subjects was 161.28 cm3 (19.48). Mean total temporal lobe volume for male and female were 169.23 cm³ (19.40) and 153.63 cm³ (16.54) respectively. Mean temporal lobe volume for the right side is ranging from 79.18 cm³ (8.25) to 87.25 cm³ (11.11) and for the left side is from 76.79 cm³ (9.42) to 84.55 cm³ (11.04). There was significant correlation between volume of hippocampus and volume of temporal lobe (r = 0.475, p < 0.01). Conclusion: These normative data for hippocampus and temporal lobe were useful reference for Malay population. There was significantly larger right hippocampus as compared to left hippocampal volume. There is fairly good association between the temporal lobe and hippocampal volume within normal adult with normal MRI brain.